The Allocation of Investment in a Dynamic Economy - Shell, Karl; Stiglitz, Joseph E. (Quarterly Journal of Economics, 1967)
I. Introduction and summary, 592.–II. The one-sector two-capital model, 593.–III. Dynamic analysis, 597.–IV. Market structure, 603.–V. Rationality and irrationality, 607.–VI. Concluding comments, 609.